INTERNET-BASED READING ASSESSMENT: OPPORTUNITIES AND CHALLENGES - Umi Rachmawati (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2016)
Assessment has become one major focus in language teaching. In relation to the curriculum and the focus of language teaching in Indonesian context, probably reading plays an important roles. To make it connected, the reading assessment has become one field that the stakeholders concerned about. It is absolutely known that administering reading assessment is not easy, one factor is the money spend in administering the reading assessment. Therefore there is a need to create more efficient and feasible reading assessment on the new contexts of the language learners. As internet and computer become common things had by most of the language learners, there is a tendency to develop reading assessment through the use of internet and computer. Internet provide not only new and recent materials, it also meets the practicality and the feasibility of the reading assessment stated before.